Developing Sign Displays for Conveying Information - Anna M. Prizzia; Mark E. Hostetler; Martin B. Main (EDIS)
The purpose of this document is to provide an overview of the four stages (planning, preparation & creation,  testing & revision, and implementation & evaluationl) in creating educational sign displays. As an illustration of this process, we discuss sign displays designed for homeowners in a residential community (Figure 1). These displays were part of an environmental education program that informed homeowners about natural resource conservation issues. This document is WEC 180 and is one of a series of the Department of Wildlife Ecology and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences (IFAS), University of Florida. First published: May 2004.